2020
DOI: 10.22302/iribb.jur.mp.v88i2.379
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based virtual screening of bioherbicide candidates for weeds in sugarcane plantation using in silico approaches

Abstract: Weeds in sugarcane have negatively affected the sugar yield rate. Several approaches have been carried out to overcome the weeds, including the usage of diuron as synthetic herbicide. However, the long-term usage of diuron is known to have a negative effect leads to the production of 3,4- Dichloroaniline responsible for soil leach and bioaccumulation. Therefore, this study aimed to find a potential natural herbicide. By mimicking the diuron's mode of action which inhibits the process of photosynthesis through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Phenolic, alkaloid, and terpenoid groups were contained in the shoot, root, and whole plant extracts of P. clematidea. Results of phytochemical screening were consistent with previous studies that P. clematidea plants contained phenolics, i.e., flavonoids (Thepphakhun and Intanon 2020); terpenoids, i.e., sesquiterpenes (Caryophyllene) and monoterpenes (Wang et al 2006;Araniti et al 2017;Zhi et al 2018) and alkaloids, i.e., aurachin A and aurachin P (Permatasari et al 2020). These secondary metabolites are found in all parts of the plant with various concentrations, but their presence depends on the plant species and environmental factors (Gomes et al 2017).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Phenolic, alkaloid, and terpenoid groups were contained in the shoot, root, and whole plant extracts of P. clematidea. Results of phytochemical screening were consistent with previous studies that P. clematidea plants contained phenolics, i.e., flavonoids (Thepphakhun and Intanon 2020); terpenoids, i.e., sesquiterpenes (Caryophyllene) and monoterpenes (Wang et al 2006;Araniti et al 2017;Zhi et al 2018) and alkaloids, i.e., aurachin A and aurachin P (Permatasari et al 2020). These secondary metabolites are found in all parts of the plant with various concentrations, but their presence depends on the plant species and environmental factors (Gomes et al 2017).…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have shown that P. clematidea extract from plant shoots inhibited seed germination and growth of weeds, such as Biden pilosa (Thepphakhun et al 2019;Intanon et al 2020) and Digitaria ciliaris (Thepphakhun et al 2019). That is due to the allelochemicals content in its extract, which comprises phenolic (Thepphakhun and Intanon 2020), terpenoid (Wang et al 2006), and alkaloid groups (Permatasari et al 2020). Praxelis allelochemicals are released into the environment through litter decomposition from plant organs (Thepphakhun et al 2019); their toxic effects only last about 1 month in the soil (Thepphakhun and Intanon 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, aurachin A and aurachin P, as well as cyanobacterin were placed in the top rating of compounds with a high-affinity index to the specified MT. The binding of the phytotoxins to protein D1 was determined by their interaction with certain amino acid residues, and the set of amino acids involved in binding turned out to be 50–90% similar to the one for its complex with diuron [ 202 ]. A complex-stage virtual screening of inhibitors of 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) was designed.…”
Section: Natural Phytotoxins As Prototypes Of Synthetic Herbicidesmentioning
confidence: 99%
“…As a result, aurachin A and aurachin P, as well as cyanobacterin were placed in the top rating of compounds with a high affinity index to the specified MТ. The binding of the phytotoxins to protein D1 was determined by their interaction with certain amino acid residues, and the set of amino acids involved in binding turned out to be 50-90% similar to the one for its complex with diuron [202]. A complex-stage virtual screening of inhibitors of 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) was designed.…”
Section: Natural Phytotoxins As Prototypes Of Synthetic Herbicidesmentioning
confidence: 99%